Implementation of Student Character Building in Hindu Religious Education for Class IX Students of SMP Petra Berkat Denpasar - Eko Adi Saputra; Ida Ayu Gede Desiana Wijaya Ningsih (International Journal of Multidisciplinary Sciences, 2023)
Education is a teaching and learning process, a habit, skill, and human knowledge that is taught from generation to generation. Meanwhile, character is the learning of character, traits and habits of individuals in everyday life. Character education is a systematic education that has the goal of instilling the expected character values ​​in students. The rapid development of globalization has made the government prioritize character education, seeing the character of the Indonesian nation decline, this can be seen from the phenomenon that has begun to leave the importance of character education. Data collection techniques used in this study were observation, interviews and documentation. The results of this study are: (1) The learning process of Hindu religious education can build students with character; (2)The results of this study will show that the application of student character building in learning Hinduism requires understanding as a curriculum implementer; (3) Increasing teacher competence in using and being a solution by prioritizing Pancasila principles in the independent curriculum, which instills Character Education in every lesson seen from religious values, independence, integrity, and mutual cooperation, and (4) Turning schools into schools that prioritize the character of students, are innovative and dynamic so that students are motivated. In this case Character Education continues to be seriously and sustainably trained in order to produce national assets and as a facilitator for students through learning activities at school, it is hoped that students will not only have good competence, but character, integrity and have commendable morals, especially at Petra Berkat Denpasar.